1982
DOI: 10.1128/jvi.44.1.209-216.1982
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus RNA-Dependent RNA Polymerase Synthesizes Full-Length Copies of Poliovirion RNA, Cellular mRNA, and Several Plant Virus RNAs In Vitro

Abstract: The poliovirus RNA-dependent RNA polymerase was active on synthetic homopolymeric RNA templates as well as on every natural RNA tested. The polymerase copied polyadenylate· oligouridylate [oligo(U)], polycytidylate · oligoinosinate, and polyinosinate· oligocytidylate templates to about the same extent. The observed activity on polyuridylate· oligoadenylate was about fourfold less. Full-length copies of both poliovirion RNA and a wide variety of other polyadenylated RNAs were synthesized by the polymerase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…Template specificity of poliovirus replicase. Previous results have shown that purified poliovirus replicase can copy a variety of poly(A)-containing RNAs in the presence of host factor or oligo(U) (5,16,44). However, with host factor, the efficiency of copying of poliovirion RNA was two-to threefold more than that of other poly(A)-containing RNAs (5, P-Ser I / P-Thr *~('?…”
Section: Resultsmentioning
confidence: 99%
“…Template specificity of poliovirus replicase. Previous results have shown that purified poliovirus replicase can copy a variety of poly(A)-containing RNAs in the presence of host factor or oligo(U) (5,16,44). However, with host factor, the efficiency of copying of poliovirion RNA was two-to threefold more than that of other poly(A)-containing RNAs (5, P-Ser I / P-Thr *~('?…”
Section: Resultsmentioning
confidence: 99%
“…Several laboratories investigating viral RdRps in vitro obtained dimer-sized RNA products. In the case of the poliovirus RdRp 3DPol protein, this phenomenon has been described and discussed by a number of different authors (Tuschall et al, 1982;Young et al, 1985;Hey et al, 1986Hey et al, , 1987Lubinski et al, 1986;Plotch et al, 1989;Neufeld et al, 1991;Cho et al, 1993). Interestingly, in the case of polioviruses and EMCVs, dimer-sized genomic RNA molecules have also been detected in vivo (Senkevich et al, 1980;Young et al, 1985), which fuels speculations that these molecules may represent intermediates in the RNA replication process.…”
Section: Discussionmentioning
confidence: 96%
“…RNA templates with alternative structures may determine whether the RdRp can initiate de novo at the initiator sequence (promoter) or it may use the 3Ј end of the template as primer. The 3Ј-terminal extension reaction ("self-priming") on the template RNA is not unique to the tombusvirus RdRp and is also generated in many in vitro RdRp systems, including TCV (Song and Simon, 1995a;Nagy et al, 1998;Nagy and Simon, 1998a,b), Poliovirus (Tuschall et al, 1982;Lubinski et al, 1986Lubinski et al, , 1987Hey et al, 1986), and Hepatitis C virus (Behrens et al, 1996).…”
Section: Figmentioning
confidence: 99%